Estudio de factibilidad para la creación de un centro geriátrico en la parroquia de Conocoto, valle de los Chillos en la ciudad de Quito - Chauca Perugachi, Lizbeth Alexandra (2010)
This draft pre-feasibility, feasibility seeks to give the idea of ​​a Geriatric Center in the Parish Conocoto Chillos Valley in the city of Quito, which allows providing comprehensive care service for elderly people in the mode of the day, that is, patients visit the center and have social, recreational, hunting activities; medical and psychological prevention in the course of the day, in the afternoon to return home in the company of their family, and in addition to patients receiving residential services outlined above with the difference that the latter live in our residential halls, the which can be visited by loved ones on weekends.